In your face! ebook - Peirce, Lincoln (Big Nate Comics, 2021)
Like a sudden soccer ball to the gut, this thrilling installment in the enormously popular Big Nate series will take your breath away! When you're a sixth-grade dynamo like Nate Wright, life comes at you fast. Whether it's a soccer ball to the head or another teacher tirade, surprises lurk around every corner. In this Big Nate collection, Nate's friends issue the ultimate insult: they point out all the ways he resembles his arch-nemesis, Gina. Nate also scores a new job as an intern at Klassic Komix, and his master plan to carpet-bomb the school with Valentine's Day cards goes seriously sideways. And when Nate gets dragged into a cringe-worthy party for the dreaded Mrs. Godfrey, what could possibly go wrong? With laughs, adventures, and jokes galore, In Your Face! will make your head spin.